Ultimate bearing behavior of H-beam welded hollow spheres under eccentric compression. (1st June 2020) - Wen, Suolin; Liu, Hongbo; Chen, Zhihua; Ying, Jiaojie
Highlights: H-beam welded hollow sphere developed buckling failure subjected to eccentric compression. The design formula of H-beam welded hollow sphere subjected to eccentric compression was proposed. The test results verified the rationality of the proposed formula. The bearing capacity of joints is greatly affected by ribbing, H-beam height, flange width, and hollow sphere size. The axial force–bending moment relationship curve of the joint is independent of its geometric size. Abstract: An H-beam welded hollow spherical joint is a new kind of spatial grid structure. In this study, the eccentric-loaded behavior of H-beam welded hollow spherical joints was studied, and the influential law of material strength, joint size, and stiffening rib on its mechanical properties was analyzed through experimental research and numerical simulation. Parametric analyses were conducted to study the eccentric-loaded behavior of H-beam welded hollow spherical joints subjected to pure bending or the combined action of axial force and bending moment using a finite element model verified through experiments. The calculation formula of the bending bearing capacity of the joints and the axial force-bending moment curve were also obtained. Finally, the design rule for eccentric compression was proposed and verified through test results.